Nature Center Learning Model on Increasing Creativity and Fine Motor Skills in Kindergarten - Sri Ayu; Triwahyuni, Eges; Kustiyowati (Universitas Pendidikan Ganesha, 2025)
Early childhood development has unique characteristics and occurs at a fundamental and rapid stage that is crucial for their future life. To support this development, it is necessary to implement the Nature Center Learning Model for children aged 5–6 years in kindergarten. However, in practice, the selection of learning models, particularly for early childhood education, is often overlooked. This study aims to examine the effect of the Nature Center Learning Model on creativity and fine motor skills of children aged 5–6 years. The research employed a quantitative approach with a quasi-experimental method. The population consisted of all kindergarten students, and the sampling technique used was Cluster Random Sampling. The results showed an Asymp. Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference in creativity before and after the implementation of the Nature Center Learning Model. Furthermore, regression test results revealed a significance value of 0.000 < 0.05, demonstrating that the model also had a significant effect on fine motor skills. Thus, the Nature Center Learning Model is proven to enhance both creativity and fine motor skills in early childhood. The implication of this research highlights the importance of applying the nature center approach in early childhood education as a strategy to optimize children’s developmental aspects.